Variation of herbicide resistant Clearfield® rice and weedy rice variants in Malaysia - Engku Ariff, Engku Ahmad Khairi; Mazlan, Norida; Anuar, Nur Hidayatul Shuhada; Juraimi, Abdul Shukor; Yusop, Mohd Rafii; Anwar, Md. Parvez (BPAS Publisher, 2014)
Weedy rice (Oryza sativa) is a major problem in South-east Asian rice growing countries. Unfortunately, there was no effective measure to control weedy rice until the introduction of herbicide resistant Clearfield® rice. The objective of this study wasto determine the variability among Clearfield® rice varieties and weedy rice variants commonly found in Malaysia in terms of seed size and vegetative growth at different growth stages.Treatments included 2 Clearfield® rice varieties namely MR220-CL1 (CL1) and MR220-CL2 (CL2) and 4 locally found weedy rice variants namely Variant 1 (V1), Variant 2 (V2), Variant 3(V3) and Variant 4 (V4). Clearfield® rice varieties were procured from MARDI Seberang Perai. The experiment was arranged in completely randomized design (CRD) with four replications. Data were collectedon seed morphology and vegetative growth. Weedy rice showed more variation compared to Clearfield® rice in terms of seed size, plant stature and tillering ability. Seeds of weedy rice were easy to shatters and had low spikelet fertility. Weedy rice seeds were found shorter but wider compared to Clearfield® rice seeds. Except for weedy rice variant V2, all other Clearfield® rice and weedy rice seeds were found slender in terms of length:width ratio. Weedy rice wasmuch taller and had more tillering ability as compared with Clearfield® rice. All these characteristic of weedy rice offer major advantages against commercial rice and thus, weedy rice is more competitive than Clearfield® rice when grown undersame agro-ecological conditions.